Juridical Review of Adultery Cases at the Sigli Syar’iyah Court (Case Study of Decision Number 12/JN/2024/MS.Sgi): Tinjauan Yuridis Terhadap Perkara Zina di Mahkamah Syar’iyah Sigli (Studi Putusan Nomor 12/JN/2024/MS.Sgi) - Rizky, M Fathir (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2024)
Aceh as the only province in Indonesia that implements Islamic sharia law, regulates adultery through Qanun Number 6 of 2014 concerning Jinayat Law. However, in practice, this qanun still faces various weaknesses, especially related to the defendant's confession which is often considered as the main evidence. This raises questions about the validity of the confession without additional evidence. In addition, the application of jinayat procedural law has also not been fully implemented in accordance with applicable provisions. This study starts from two main problem formulations: how is the application of the defendant's confession in the Aceh Qanun Jinayat related to adultery, and how is the legal review of the implementation of decisions in adultery cases at the Sigli Syar'iyah Court based on Qanun Number 6 of 2014 and Qanun Number 7 of 2013 concerning Jinayat Procedural Law. The study uses a normative legal method with a statutory, case, and sociological approach. Primary data was obtained from an official copy of Decision Number 12/JN/2024/MS.Sgi, while secondary data includes legal literature, academic journals, qanuns, and other supporting documents. The results of the study indicate that the defendant's confession is the main evidence underlying the determination of the sentence, although this approach is prone to problems if the confession is obtained without ensuring the defendant's freedom from pressure. Community involvement in raids, which are often carried out without formal legal procedures, triggers a violation of the defendant's privacy. The destruction of evidence in the form of the defendant's cellphone is also considered less relevant because the item did not have a direct role in the crime. Therefore, an evaluation of the jinayat legal mechanism in Aceh is needed, especially in terms of evidence, community involvement, and management of evidence, to ensure a more just, humane, and consistent application with the teachings of Islam which is rahmatan lil 'alamin.